Deep Carbon Past to Present - Orcutt, Beth N.; Daniel, Isabelle; Dasgupta, Rajdeep (Physical Sciences, 2019)
Summarizing ten years of research by the Deep Carbon Observatory, this is a comprehensive guide to carbon inside Earth - its quantities, movements, forms, origins, changes over time, and impact on planetary processes - for students and researchers in Earth and planetary sciences. Also available as Open Access on Cambridge Core.